2022
DOI: 10.1002/cam4.5005
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of tumor‐derived extracellular vesicles in the treatment of malignant pleural effusion

Abstract: Vesicles, also known as “microparticles”, are vesicle‐like structures that are released outside the cell in a “sprouting” manner when the cytoskeleton is changed during cell activation or apoptosis, with a diameter of about 100–1000 nm, and are carriers of material information exchange between cells. Tumor‐derived extracellular vesicles can effectively deliver drugs to the nucleus of tumor stem cells, thus effectively killing them without toxic side effects. The underlying mechanism involves the soft nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…Tumor immunotherapy is an effective strategy for tumor control that efficiently treats malignant pleural effusion by mobilizing the maximum number of neutrophils in the body, highlighting the special features of drug-loaded vesicles in tumor immunotherapy. The most recent clinical trial showed promising results in the treatment of malignant ascites, indicating that drug-loaded T-MPs are universally effective in treating clinical malignant pleural effusion [ 52 , 69 ].…”
Section: Dual Significance Of T-mps In Immune System Regulationmentioning
confidence: 99%
“…Tumor immunotherapy is an effective strategy for tumor control that efficiently treats malignant pleural effusion by mobilizing the maximum number of neutrophils in the body, highlighting the special features of drug-loaded vesicles in tumor immunotherapy. The most recent clinical trial showed promising results in the treatment of malignant ascites, indicating that drug-loaded T-MPs are universally effective in treating clinical malignant pleural effusion [ 52 , 69 ].…”
Section: Dual Significance Of T-mps In Immune System Regulationmentioning
confidence: 99%